CURRENT CHALLENGES OF STRATEGY USE IN SECOND LANGUAGE TEACHING: A CASE OF PUBLIC PRIMARY SCHOOLS IN TANZANIA - Kotira, Salome; Shizhou, Lou (African Journal of Education and Practice, 2022)
Purpose: The main purpose of this study was to examine how the teaching challenges affect strategy use in second language classrooms in Tanzanian public primary schools, mainly in Manyara region. In the process of teaching second language teachers uses different strategies of teaching so they can help their students acquire a target language. There are some challenges that hinder the teaching process and caused the teaching strategies to be ineffective. Methodology: This particular study has used the qualitative approach method of which the descriptive method was applied. The data were collected through observation and interviews to investigate on those challenges and how it affects the teaching strategies in the second language classrooms. The 24 teachers from 46 teachers who teach Kiswahili and English languages of the three primary schools were randomly selected from Acronis, Engonongoi and Loorng'oswani located in Manyara region have been the participants of this research. Findings: The results of this study revealed that second language teaching in the classrooms faces different challenges in the use of strategies of teaching. Challenges that are been found are overcrowded classroom, lack of teaching materials and teachers' poor knowledge on how students acquire second language. Unique contribution to theory, practice and policy: This study has found that teaching challenges are what make second-language teaching strategies to be ineffective. The results of this study will help language and education stakeholders to address these challenges in order the teaching strategies to be more effective when employed in the classroom. The study suggested that the general improvement of primary school classrooms should be conducted to fix this problem. The number of second language teachers should be increase to fit the number of students. These schools have divided their students in different classrooms but because there is shortage of teachers they have to put them in one classroom when they are teaching.